Determination of Potential in Pratama Taro (Colocasia esculenta (L). Schott var. Pratama) in Sumedang District, Bandung Regency, Indonesia - Gunawan, Wawan; Putra, Ramadhani Eka; Pujo, Pujo; Rohmat, Farhan Ilham Wira; Hanifah, Dini Siti; Awaliyah, Fitri; Anggraeni, Raden Dewi; Nuradzkia, Nida (Journal of Agri-Food Science and Technology, 2025)
Bandung Regency has several types of cultivated taro, with the largest production center in the Sumedang District. Semir Taro (TS0) is one of the native commodities in this region, and the other types are from the crossbreeding process between Semir Taro and Thai Silk Taro, which is named Pratama Taro (TS1 & TS2). Although it has been widely marketed and consumed by the public, the nutrient content value of this type of taro is still unknown. In addition, TS1 and TS2 have the potential to be developed into products that have higher economic value if processed optimally. This study contributes to determining the nutritious content of three taro varieties and identifies the most appropriate raw materials for the production of taro-derived products. The methods used were chemical analysis and affective organoleptic tests with paired comparison. Organoleptic tests were carried out on TS1 and TS2, and they were steamed to determine whether there was a difference between the two taros. The results of the test showed that there was no difference in the colour, aroma, and texture parameters of the two taros, but there was a difference in taste between them. While the results of the chemical analysis show that the three types of taros have a reasonably good nutrient content, because the water content is relatively high, there need to be post-harvest management efforts so that taro can be a more durable product for storage.